Students’ Perception Toward English Zone In English Study Program of Iain Curup - Maya Sari Setyowati (Journal of English Education and Teaching, 2019)
The objectives of this research was to know  students’ perception toward English Zone at English Study Program of IAIN Curup. The study is a descriptive research presented quantitativelly. The population of this research all students in all semester at English Study Program by using random sampling, total of the student was 37 students. From the population the researcher take students’ from second, fourth, sixth, and eighth semester because they are studying at English Zone. Data were collected through questionnaire. The data were analiyzed by using tabulating and making percentage. There were two indicators, difficulties and benefits of using English in English Zone. The first indicator, from 9 statements got 5 negative perception and 4 positive perception with total 49,48 percentages. Furthermore, the second indicator got 0 negative perception and 7 positive perception with total 50,52 percentages. The result shows that the majority of students’ perception was in positive category toward English Zone. In conclusion students’ perception toward English zone is positive perception to increase their ability in English. However, there are students’ problems using English cause by several factors. There are inhibition, nothing to say, low or uneven participation, and mother tongue use.